Design and Implementation of Fire Fighting Robot - Rodi Hartono (Program Studi Teknik Elektro, Fakultas Teknik dan Ilmu Komputer, Universitas Komputer Indonesia., 2013)
Abstract – The development of technologytodaygrows rapidly, people need strong machines that can operate continously and can operate in a dangerous condition. In this journal made an intelligent fire fighting robot that can extinguish fire in a specific condition. In this design, the field of fire modelled in a labyrinth. Dimension of labyrinthis 2.5x2.5 meters, the wall will be in 33 centimeters and there will be four rooms. Candle will be placing on a random position. The robot will active if hear the fire alarm from sound activation. The robot move from home and will search and check every room. If the robot find the candle, then the robot will extinguish the fire at save position. Less time spendingfor searching and extinguish the fire is a main target in this design. After extinguish the fire the robot should back home.